ROLE OF COLORS IN DESIGN WEB BANNER ADVERTISING: IN THE CONTEXT OF ETHNIC APPAREL - Majumdar, Ankita (International Journal of Research -GRANTHAALAYAH, 2014)
Since the first banner ad spanned the top of the Hot Wired web site in 1994, and internet advertising expenditures have seen triple digit growth to around three billion dollars per year. Although limited in size to 468 by 60 pixel, banner ads are the main form of advertising on the web and today’s scenario it is one of the most prolific form of marketing used in online world. All companies use them in one form or another because they are an affordable, measurable and effective medium to increase Brand awareness and Brand equity. The web is a colorful place, and there is a lot that can be accomplished by using color in the right way, at the right time, with the right audience, and for the right purpose. Therefore it turns out that color is one of the most exciting things in the world.